Volumetric laser endomicroscopy features of dysplasia at the gastric cardia in Barrett's oesophagus: results from an observational cohort study. Issue 1 (23rd October 2019) - Trindade, Arvind J; Raphael, Kara L; Inamdar, Sumant; Stewart, Molly; Berkowitz, Joshua; Vegesna, Anil; McKinley, Matthew J; Benias, Petros C; Kahn, Allon; Leggett, Cadman L; Lee, Calvin; Sejpal, Divyesh V; et al.
Abstract : Objective: Volumetric laser endomicroscopy (VLE) is an advanced imaging modality used in Barrett's oesophagus (BE) to help identify dysplasia in the oesophagus. VLE criteria exist for oesophageal dysplasia but not for dysplasia in the gastric cardia. The aim of this study was to determine if there are in vivo VLE features that can predict gastric cardia dysplasia in BE. Design: This was a single-centre observational cohort study from August 2016 to August 2018. Patients were included if they had BE, were undergoing a VLE exam as standard of care, and had a suspicious target laser marked at the gastric cardia. The following VLE features were correlated to histology to determine if an association existed between histology subtype and VLE feature: wide crypts, irregular surface, one large isolated gland, multiple glands, and complex glands. Results: A total of 110 in vivo gastric cardia targets in 77 patients with BE were analysed. The following abnormalities were identified: 61 wide crypts, 34 isolated glands, 16 irregular surfaces, 15 multiple glands, and 11 complex glands. Complex glands were the only VLE feature that correlated to any histology subtype. They were present in 71% of targets with high-grade dysplasia (HGD), T1a cancer or T1b cancer and had a sensitivity, specificity, and accuracy of 71%, 99%, and 85%, respectively. Of the 10 patients with complex glands on VLE and HGD/cancer on histology, 4 had a normal-appearing mucosa (40%) on endoscopy. Conclusion: Identification of complex glands on VLE may aid in detection of HGD or early cancer in the gastric cardia in BE. This is particularly important, as dysplasia at the gastric cardia can be difficult to see endoscopically.